Rate of Oxidation of Thiamine by Hg(II) in Alkaline Medium - H. Hina, Rateb (Asian Journal of Chemistry, 2010)
A differential kinetic spectrophotometric method is proposed for studying the rate of oxidation of thiamine, TM (vitamin B1) by mercury(lI) in basic medium (pH = 12.5). The reaction has been studied in the range of 277.7 K to 320.5 K. The concentration of thiamine used: 0.35 x 10-5 M, 0.70 X 10-5 M and 1.40 x 10-5 M. The concentrations of OH- and Hg(Il) were kept constant by using 2 M NaOH and 2.0 x 10-3 M Hg(lI). Under these conditions, the only reaction product detected was thiochrome (TC). The initial rate was followed by recording the rate of formation of TC at λ = 350 nm for the first 20 seconds. Different kinetic parameters have been measured under reaction conditions.